Alcohol, Methamphetamine, and Marijuana Exposure Have Distinct Effects on the Human Placenta. (April 2016) - Carter, R. Colin; Wainwright, Helen; Molteno, Christopher D.; Georgieff, Michael K.; Dodge, Neil C.; Warton, Fleur; Meintjes, Ernesta M.; Jacobson, Joseph L.; Jacobson, Sandra W.
Abstract : Background: Animal studies have demonstrated adverse effects of prenatal alcohol exposure on placental development, but few studies have examined these effects in humans. Little is known about effects of prenatal exposure to methamphetamine, marijuana, and cigarette smoking on placental development. Methods: Placentas were collected from 103 Cape Coloured (mixed ancestry) pregnant women recruited at their first antenatal clinic visit in Cape Town, South Africa. Sixty‐six heavy drinkers and 37 nondrinkers were interviewed about their alcohol, cigarette smoking, and drug use at 3 antenatal visits. A senior pathologist, blinded to exposure status, performed comprehensive pathology examinations on each placenta using a standardized protocol. In multivariable regression models, effects of prenatal exposure were examined on placental size, structure, and presence of infections and meconium. Results: Drinkers reported a binge pattern of heavy drinking, averaging 8.0 drinks/occasion across pregnancy on 1.4 d/wk. 79.6% smoked cigarettes; 22.3% used marijuana; and 17.5% used methamphetamine. Alcohol exposure was related to decreased placental weight and a smaller placenta‐to‐birthweight ratio. By contrast, methamphetamine was associated with larger placental weight and a larger placenta‐to‐birthweight ratio. Marijuana was also associated with larger placental weight. Alcohol exposure was associated with increased risk of placental hemorrhage. Prenatal alcohol, drug, and cigarette use were not associated with chorioamnionitis, villitis, deciduitis, or maternal vascular underperfusion. Alcohol and cigarette smoking were associated with a decreased risk of intrauterine passing of meconium, a sign of acute fetal stress and/or hypoxia; methamphetamine, with an increased risk. Conclusions: This is the first human study to show that alcohol, methamphetamine, and marijuana were associated with distinct patterns of pathology, suggesting different mechanisms mediating their effects on placental development. Given the growing body of evidence linking placental abnormalities to neurodevelopmental deficits, these findings may be important in the long‐term teratogenic effects of prenatal alcohol and drug exposure. Abstract : In a prenatally recruited, prospective longitudinal cohort, alcohol exposure was related to decreased placental weight and a smaller placenta‐to‐birthweight ratio. By contrast, methamphetamine was associated with larger placental weight and a larger placenta‐to‐birthweight ratio; marijuana with larger placental weight. This is the first study to demonstrate distinct alcohol‐, methamphetamine‐, and marijuana‐related patterns of placental pathology. Given evidence linking placental abnormalities to neurodevelopmental deficits, these findings may be important in the teratogenic effects of prenatal alcohol and drug exposure.